Development of the Emo Path Educational Game Media in Group Counseling Services to Help Flood Survivor Students Express Their Emotions - Klara Putri Ningsih; Nefi Darmayanti (Journal of Society Counseling, 2026)
This study aims to develop an educational media game called Emo Path for use in group counseling to help flood survivor students express their emotions. The study is motivated by findings showing that students affected by floods often have difficulty expressing emotions such as fear, sadness, anxiety, and trauma due to disaster-related experiences. This research uses a Research and Development (R&D) Level 1 approach with a 4D development model, limited to the define, design, and develop stages. The study was carried out at UPT SMP Negeri 17 Medan, involving 18 flood survivor students from grades VII, VIII, and IX, selected through purposive sampling. Data was collected through a needs analysis questionnaire, validation instruments from content and media experts, and a student response questionnaire. The data was analyzed using quantitative and qualitative descriptive techniques with a Likert scale. The needs analysis results showed that students really need game-based educational media in group counseling services, with agreement percentages ranging from 61.1% to 72.2%. The content expert validation scored 93.2%, while the media expert validation reached 94.2%, both of which fall into the very feasible category. Meanwhile, the practicality test conducted on students scored 87.8%, indicating that the media is very practical to use. The research findings show that the Emo Path Game is a feasible and practical tool to use in group counseling services to help student flood survivors express their emotions more openly, safely, and adaptively. The novelty of this study lies in the development of an educational game specifically designed based on the emotional experiences of student flood survivors, as well as in the integration of event cards, emotion expression cards, and value reflection cards into a unified counseling game framework.